Students’ Responses to the Implementation of Word Wall in Vocabulary Learning - Pertiwi, Aulia Putri; Yanto, Elih Sutisna; Abas, Totoh Tauhidin (STKIP Yapis Dompu, 2022)
Vocabulary is one of the main elements in English. because mastery of vocabulary is very important in learning English, one method that can be used in teaching vocabulary is through word walls. The purpose of this study was to describe the responses of class VIII students in one of the junior high schools in Karawang using the word wall technique in vocabulary learning. This study was conducted to see whether the use of word walls is effective in learning vocabulary. The design of this research uses a case study. These results indicate that the use of vocabulary in vocabulary learning gets a positive response from students. They feel that by using the word wall their vocabulary increases and they are motivated to continue learning English. But there are drawbacks to the use of word walls in vocabulary learning, namely, it takes a long time to make word walls and the cost is quite expensive. To conclude, using the word wall technique in students' vocabulary learning positively affected them; it improved their vocabulary learning and motivated them to continue using it.